2021
DOI: 10.7759/cureus.13952
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Burden of Delayed Hip Fracture Surgery: A Single-Center Experience

Abstract: Fragility hip fractures have become a worldwide epidemic with serious socioeconomic implications. The projected number of hip fractures by 2050 is estimated to reach 4.5 million cases. The aim of this study was to calculate the in-hospital financial burden on public health insurance funds related to the delayed treatment of hip fractures. This research took place in a tertiary university hospital that is a major trauma center in Thessaloniki, which is second largest city in Greece . A retrospective search was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The harmful effects of perioperative heart failure make it an important problem in the healthcare system. Previous studies showed that perioperative acute heart failure (AHF) substantially increased mortality within 30 days after surgery to 65%, prolonged the average length of stay of patients by 4 days, and increased the average hospitalization cost by about 5500 euros [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The harmful effects of perioperative heart failure make it an important problem in the healthcare system. Previous studies showed that perioperative acute heart failure (AHF) substantially increased mortality within 30 days after surgery to 65%, prolonged the average length of stay of patients by 4 days, and increased the average hospitalization cost by about 5500 euros [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A demographic survey of femoral pertrochanteric fractures provides several important information for the healthcare system of a country. First, pertrochanteric fractures rank as one of the most common surgically treated injuries in the elderly population, considering that the incidence of hip fractures is projected to reach six million globally by 2050 [ 1 ]. Second, the poor functional prognosis related to pertrochanteric fractures has been a burden on society, where 20%-30% of patients die within a year postoperatively and 50%-60% suffer from disability.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of femoral pertrochanteric fractures among elderly patients is steadily rising on a global scale [1]. Consequently, it becomes imperative for surgeons to bestow due diligence upon the application of a precise preoperative imaging classification system, as it profoundly impacts postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%